Formation of giant iron oxide-copper-gold deposits by superimposed, episodic hydrothermal pulses - Irene Del Real (Nature Portfolio, 2021)
The Candelaria iron oxide-copper-gold deposit in Chile was formed by superimposed, episodic hydrothermal pulses with contrasting composition and temperature, according to micro-textural and compositional variations in actinolite, a common alteration mineral.